T cells and reactive oxygen species - Aleksey V. Belikov; Burkhart Schraven; Luca Simeoni (2015)
Reactive oxygen species (ROS) have been long considered simply as harmful by-products of metabolism, which damage cellular proteins, lipids, and nucleic acids. ROS are also known as a weapon of phagocytes, employed against pathogens invading the host. However, during the last decade, an understanding has emerged that ROS also have important roles as signaling messengers in a multitude of pathways, in all cells, tissues, and organs. T lymphocytes are the key players of the adaptive immune response, which both coordinate other immune cells and destroy malignant and virus-infected cells. ROS have been extensively implicated in T-cell hyporesponsiveness, apoptosis, and activation. It has also become evident that the source, the kinetics, and the localization of ROS production all influence cell responses. Thus, the characterization of the precise mechanisms by which ROS are involved in the regulation of T-cell functions is important for our understanding of the immune response and for the development of new therapeutic treatments against immune-mediated diseases. This review summarizes the 30-year-long history of research on ROS in T lymphocytes, with the emphasis on the physiological roles of ROS.